Myo-inositol oxygenase is required for responses to low energy conditions in Arabidopsis thaliana - Alford, Shannon R.; Rangarajan, Padma; Williams, Sarah P.; Gillaspy, Glenda E. (Frontiers in Plant Science, 2012)
myo-Inositol is a precursor for cell wall components, is used as a backbone of myo-inositol trisphosphate (Ins(1,4,5)P3) and phosphatidylinositol phosphate signaling molecules, and is debated about whether it is also a precursor in an alternate ascorbic acid synthesis pathway. Plants control inositol homeostasis by regulation of key enzymes involved in myo-inositol synthesis and catabolism. Recent transcriptional profiling data indicate up-regulation of the myo-inositol oxygenase (MIOX) genes under conditions in which energy or nutrients are limited. To test whether the MIOX genes are required for responses to low energy, we first examined MIOX2 and MIOX4 gene expression regulation by energy/nutrient conditions. We found that both MIOX2 and MIOX4 expression are suppressed by exogenous glucose addition in the shoot, but not in the root. Both genes were abundantly expressed during low energy/nutrient conditions. Loss-of-function mutants in MIOX genes contain alterations in myo-inositol levels and growth changes in the root. Miox2 mutants can be complemented with a MIOX2:green fluorescent protein fusion. Further we show here that MIOX2 is a cytoplasmic protein, while MIOX4 is present mostly in the cytoplasm, but also occasionally in the nucleus. Together, these data suggest that MIOX catabolism in the shoot may influence root growth responses during low energy/nutrient conditions.